Pengembangan E-Book Fiqih Berbasis Aplikasi Sigil untuk Meningkatkan Minat Belajar di Kelas X MA Salafiyah Syafi’iyah Mojokerto - Farrihah, Rifdatul ‘Aisyil; Aisa, Aufia; Rahmawati, Rina Dian (Lembaga Yasin AlSys, 2025)
This research is motivated by the fact that the use of learning media in schools is still dominated by conventional methods such as lectures. So that students interest in reading decreases. Therefore, this research was conducted with the aim of developing an interactive multimedia-based e-book using the sigil application as a fiqh learning media for class X students. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were 32 students in class X MA Salafiyah Syafi'iyah. The data instruments used were interviews, questionnaires, and tests. Data analysis techniques consisted of expert validation data analysis, product trial data analysis, and analysis of student learning outcomes. Based on the results of the validation, namely material expert validation and media expert validation, the category was very feasible as a learning medium with a value of 85%. The results of the trial of the E-book product used can increase students' interest in learning through the E-book feasibility questionnaire which received a very feasible category with a value of 90.71%. This is proven by the increase in the influence of the use of interactive multimedia E-books on student learning outcomes from the pre-test (59.8438) and post-test (74.8438) of students and the results of the analysis using the t-test (paired) obtained a significant value of 0.001 <0.05 from the use of Interactive Multimedia-based E-books using the Sigil Application in Fiqh learning.